KECERDASAN EMOSIONAL, KEMATANGAN SOSIAL, SELF-ESTEEM, DAN PRESTASI AKADEMIK MAHASISWA LULUSAN PESANTREN - Latifah, Melly; Hernawati, Neti; Nurhayati, Suci (Jurnal Ilmu Keluarga dan Konsumen, 2011)
The purpose of this research was to analyze the difference of emotional intelligence, social maturity, self-esteem, and academic achievement on Islamic dan nonIslamic boarding graduate students; the correlation between research variables; and influence of graduate students and family’s characteristics, emotional intelligence, social maturity, and self-esteem toward academic achievement. This research involved 100 college students that were selected systematic randomly. Data were collected by interview and self report with questionnaire. The data were analyzed using descriptive, different test, correlation test, and regression test. The results showed that there were no significant differences between emotional intelligence, social maturity, self-esteem, and academic achievement between Islamic boarding and nonIslamic boarding graduate students. Emotional intelligence and social maturity had significant and positive correlation with self-esteem. Academic achievement of Islamic boarding graduate students was influenced by emotional intelligence and social maturity. While in the nonIslamic boarding graduate students, academic achievement was influenced by student activities.